Model Penerapan Green Construction Project Management dan Pendekatan Aspek Green Construction pada Proyek Konstruksi - Supriyanti , Dipa (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Green construction refers to structures and processes that are environmentally responsible and save resources. The future of green construction is full of opportunities for us to undo some of the damage we have done to the planet and the environment. The purpose of this research design is to find out whether the contractor implementing construction projects in the field applies green construction or not. To find out the application, a research design was carried out on the application of a combination between green construction project management with green construction aspect. The process of evaluating construction projects is carried out through direct discussions or using questionnaires to be filled out by project managers or who have an equivalent ability in the field of construction projects. The results to be obtained of this research are the contractor keep carry out disciplined and sustainable objectives of the incorporation of these aspects. For this reason, it is necessary to design a process of transfer of knowledge for contractors in environmentally friendly construction process activities.